Decreased circulating dipeptidyl peptidase-4 activity after short-term intensive insulin therapy predicts clinical outcomes in patients with newly diagnosed type 2 diabetes - Chen, Jie; Dai, Peiji; Ke, Weijian; Wan, Xuesi; Liu, Juan; Xu, Lijuan; Xiao, Haipeng; Li, Yanbing; Liu, Liehua (Frontiers in Endocrinology, 2024)
Background This study aims to investigate the changes in circulating dipeptidyl peptidase-4 (DPP-4) activity following short-term intensive insulin therapy (SIIT) in newly diagnosed type 2 diabetes (T2D) patients and to assess its potential in predicting long-term remission. Methods Ninety-five patients underwent SIIT for 2-3 weeks to attain and sustain near-normal glycemia. Insulin was then discontinued, and patients were followed for a year to evaluate glycemic outcomes. Biochemical tests, serum DPP-4 activity, and mixed meal tolerance tests were conducted at baseline, post-SIIT, and the 3-month follow-up. Results DPP-4 activity decreased from 44.08 ± 9.58 to 40.53 ± 8.83 nmol/min/mL after SIIT (P<0.001). After three months post-SIIT, DPP-4 activity remained stable in the remission group (39.63 ± 8.53 nmol/L) but increased in the non-remission group (42.34 ± 6.64 nmol/L). This resulted in a more pronounced decrease in DPP-4 activity from baseline in the remission group (-3.39 ± 8.90 vs. -1.10 ± 8.95, P = 0.035). Logistic regression analyses showed that patients with greater DPP-4 activity reduction had a higher likelihood of 1-year remission (70% vs. 51.1%, OR: 7.939 [1.829, 34.467], P = 0.006 in the fully adjusted model). A non-linear relationship between △DPP-4 and 1-year remission rate was observed, with a clear threshold and saturation effect. Conclusion Circulating DPP-4 activity significantly decreases after SIIT. The change in circulating DPP-4 activity during the 3-month post-treatment phase has the potential to predict long-term remission.